Searching for momentum in NBA triplets of free throws - Morgulev, E.; Azar, O. H.; Bar-Eli, M. (Journal of Sports Sciences, 2020)
The literature on momentum is still undecided, with mixed results whether momentum exists or is only perceived to exist ("hot hand fallacy"). We explore whether momentum exists by looking at cases in which a basketball player has three consecutive free throws. A free throw is a well-defined task executed in a stable environment, allegedly giving momentum optimal chances to occur. Taking 14 NBA seasons we collected over 4500 three-free-throw sets (triplets). We obtained the outcomes of the shots as well as some additional variables about the player and the game: the player`s average free-throw percentage, home or away, and the game score and the quarter when the free throws were attempted. We first analyse the hit rates in the three shots and then proceed to regression analysis that also controls for the abovementioned variables. We address several concerns raised in the literature. All comparisons and analyses yield the same conclusion that there is no evidence for momentum in the data.